Surgical Anatomy of the Gastrointestinal Tract and Its Vasculature in the Laboratory Rat - Katarína Vdoviaková; Eva Petrovová; Marcela Maloveská; Lenka Krešáková; Jana Teleky; Mario Zefanias Joao Elias; Darina Petrášová (Gastroenterology Research and Practice)
The aim of this study was to describe and illustrate the morphology of the stomach, liver, intestine, and their vasculature to support the planning of surgical therapeutic methods in abdominal cavity. On adult Wistar rats corrosion casts were prepared from the arterial system and Duracryl Dental and PUR SP were used as a casting medium and was performed macroscopic anatomical dissection of the stomach, liver, and intestine was performed. The rat stomach was a large, semilunar shaped sac with composite lining. On the stomach was very marked fundus, which formed a blind sac (saccus cecus). The rat liver was divided into six lobes, but without gall bladder. Intestine of the rat was simple, but cecum had a shape as a stomach. The following variations were observed in the origin of the cranial mesenteric artery. On the corrosion cast specimens we noticed the presence of the anastomosis between middle colic artery (a. colica media) and left colic artery (a. colica sinistra). We investigated the second anastomosis between middle colic artery and left colic artery. The results of this study reveal that the functional anatomical relationship between the rat stomach, liver and intestine is important for the development of surgical research in human and veterinary medicine.